The Canadian Pentecostal experience - Wilkinson, Michael; Ambrose, Linda McGuire (Global Pentecostal and charismatic studies, 2025)
The Canadian Pentecostal Experience includes eighteen essays organized into three themes: 1. Historiography and Early Canadian Pentecostalism; 2. Theological Practices and Processes; and 3. Social and Cultural Change. This collection makes a significant contribution to the growing literature of global Pentecostal scholarship. The works are important for the Canadian context but as the editors argue in the Introduction, Canadian Pentecostalism is "glocal" (shaped by both local and global realities). This collection will interest readers drawn from the wider field of religious studies and global Pentecostalism to initiate conversations about how Pentecostalism evolves in both its local and global expressions--